HUBUNGAN KECERDASAN EMOSIONAL DENGAN HASIL BELAJAR MATERI KERAGAMAN SOSIAL BUDAYA MASYARAKAT KELAS V SDN KEPUH KIRIMAN 1 WARU SIDOARJO - Rachmawati, Wulandjani; Sulistyawati, Ida; Satianingsih, Rarasaning (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2023)
Education is very important for all humas, especially to add insight. In the context of the world of education, students need to have satisfactory learning outcomes. Learning outcomes are stimulated through inner and external factors. These inner factors consist the intelligence of students. In this study the authors use emotional intelligence as the focus of research. The motive of this study became performed to decide the connection between emotional intelligence and learning outcomes on social and cultural diversity class V SDN Kepuh Kiriman 1 Waru Sidoarjo. This observe use a quantitative studies approach with a correlational studies design and includes a kind of survey studies. The subject of this study was class V-A SDN Kepuh Kiriman I Waru Sidoarjo. Statistics series methods used are questionnaires and assessments. The information evaluation approach use is product moment correlation. The results of the product moment correlation assessments concluded that “There Is a Relationship Between Emotional Intelligence And The Results Of Learning Material On The Socio-Cultural Diversity Of The Class V Community Of SDN Kepuh Kiriman I Waru Sidoarjo.”